DIVERSIFICATION OF MANAGEMENT ACTIVITIES AS A COMPONENT OF THE PROFESSIONAL COMPETENCE OF FUTURE SOCIAL WORKERS - Крупенко, І.М.; Падалка, В.В.; Падалка, В.М. (SWorldJournal, 2025)
The article highlights the factors influencing the nature of the professional activity of future social workers. It is determined that in the activities of students there is a process of transition to diversification, regionally-oriented options. It is em